ACP-EU Update: PUMA, weather satellite data for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The European Meteosat Second Generation (MSG) weather satellite programme is expected to transform national meteorological services in Africa.